Mommy Care: Inovasi Cerdas untuk Monitor Kondisi Ibu Hamil dengan Mikrokontroler dan Aplikasi - Erlangga Erlangga; Delfita Sari; Angga Saputra; Ayu Kartika Puspa; Yuthsi Aprilinda (Universitas Bandar Lampung (UBL), 2023)
Mommy Care: Smart Innovation for Monitoring Pregnant Women’s Condition with Microcontroller and Application - Pregnancy is an important moment in a woman’s life. Therefore, monitoring the health of pregnant women is very important. This study aims to develop an application called Mommy Care that can make it easier for pregnant women to perform health checks quickly and gradually without being limited by space and time. This application is integrated with a microcontroller equipped with temperature, blood pressure, and heart rate sensors. The test results show that the designed device can work well and provide accurate health information. Thus, it can be said that the designed device can be used well and reliably. This study contributes to the development of e-health technology that can improve the quality of life and health of pregnant women in Indonesia.